Methane cracking as a bridge technology to the hydrogen economy. (5th January 2017) - Weger, Lindsey; Abánades, Alberto; Butler, Tim
Abstract: Shifting the fossil fuel dominated energy system to a sustainable hydrogen economy could mitigate climate change through reduction of greenhouse gas emissions. Because it is estimated that fossil fuels will remain a significant part of our energy system until mid-century, bridge technologies which use fossil fuels in an environmentally cleaner way offer an opportunity to reduce the warming impact of continued fossil fuel utilization. Methane cracking is a potential bridge technology during the transition to a sustainable hydrogen economy since it produces hydrogen with zero emissions of carbon dioxide. However, methane feedstock obtained from natural gas releases fugitive emissions of methane, a potent greenhouse gas that may offset methane cracking benefits. In this work, a model exploring the impact of methane cracking implementation in a hydrogen economy is presented, and the impact on global emissions of carbon dioxide and methane is explored. The results indicate that the hydrogen economy has the potential to reduce global carbon dioxide equivalent emissions between 0 and 27%, when methane leakage from natural gas is relatively low, methane cracking is employed to produce hydrogen, and a hydrogen fuel cell is applied. This wide range is a result of differences between the scenarios and the CH4 leakage rates used in the scenarios. On the other hand, when methane leakage from natural gas is relatively high, methane steam reforming is employed to produce hydrogen and an internal combustion engine is applied, the hydrogen economy leads to a net increase in global carbon dioxide equivalent emissions between 19 and 27%. Highlights: Methane cracking-hydrogen economy has the potential to mitigate climate change. Up to 27% global CO2 -eq emissions decrease by methane cracking-hydrogen economy. Strong influence of CH4 leakage from natural gas system on total global emissions.